Оцінка та сучасні тренди забезпечення продовольчої безпеки України - Кузьома, Віталій Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Забезпечення продовольчої безпеки країни – важливе завдання для національних агропродовольчих систем. У статті проведено дослідження сучасного стану внутрішнього самозабезпечення населення України продовольством. Здійснена аналітична оцінка обсягів та динаміки експортно-імпортних операцій з сільськогосподарською сировиною та продовольчими товарами. Надано оцінка рівня покриття експортом імпорту за основними видами продовольчих товарів. Досліджено місце України у світовому рейтингу продовольчої безпеки на основі міжнародного індексу GFSI. Виявлено ключові проблеми і причини, які визначили зниження рейтингових позицій України та рівня продовольчої безпеки її населення. Здійснено аналіз окремих показників результативності розвитку аграрного сектора країни, як базису забезпечення продовольчої безпеки. Досліджено сучасна структура виробництва основних видів сільськогосподарської продукції за категоріями виробників. Узагальнено ключові тенденції, що супроводжують процеси забезпечення продовольчої безпеки України за сучасних умов. За середніми значеннями індикаторів фактичного споживання проаналізовано стан забезпечення населення основними видами продуктів харчування. Обґрунтовано пріоритетні напрями забезпечення та зміцнення продовольчої безпеки у національному масштабі.

The research on Ukraine's food security is of paramount importance, as it directly impacts the national agro-food systems. The article delves into the current state of internal food self-sufficiency in the Ukrainian population, conducting an analytical assessment of export-import transactions with agricultural raw materials and food products. The findings reveal a significant trend of increasing food exports in recent years, along with an evaluation of the export-import coverage for the main types of food products. Ukraine's place in the world rating of food security based on the Global Food Security Index was studied. The fundamental problems and reasons that determined Ukraine's decrease in the rating positions and the level of food security of its population were identified. In addition to the military conflict, Ukraine has a low economic availability of food products for the population and a low level of sustainability in the domestic agro-food system. Despite the war's consequences, the agricultural business remains one of the most profitable economic activities in Ukraine. This analysis of individual indicators of the effectiveness of the country's agrarian sector as a basis for ensuring food security underscores the sector's potential. The modern production structure of the main types of agricultural products by categories of producers was studied. The key trends accompanying ensuring food security in Ukraine under modern conditions are summarized. It was revealed that food security in the crop sector is achieved at the expense of the public sector agrarian formations, mainly at the expense of households in the livestock sector. Based on the average values of the actual consumption indicators, the state of providing the population with the main types of food was analyzed. The results showed problematic aspects in providing the country's population with meat and dairy products, fish, fruits, berries, and grapes. The priority directions for ensuring and strengthening food security on a national scale are substantiated. Among the main ones, the following are highlighted: the need to implement sustainable farming and animal husbandry practices, further improvement of the food quality management and control system, protection of biodiversity of ecological agrosystems, optimization and reduction of value chains, increasing the level of social responsibility of food producers and consumers.
Assessment and current trends of ensuring food security in Ukraine
Keywords: продовольство; експорт; сільськогосподарська продукція; самозабезпечення; агропродовольча система; агросектор; food; export; agricultural products; self-sufficiency; agro-food system; agricultural sector